2013
DOI: 10.1016/j.apsusc.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Surface roughness reduction using spray-coated hydrogen silsesquioxane reflow

Abstract: a b s t r a c tSurface roughness or texture is the most visible property of any object, including injection molded plastic parts. Roughness of the injection molding (IM) tool cavity directly affects not only appearance and perception of quality, but often also the function of all manufactured plastic parts. So called "optically smooth" plastic surfaces is one example, where low roughness of a tool cavity is desirable. Such tool surfaces can be very expensive to fabricate using conventional means, such as abras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…Studies have shown that the surface roughness of materials strongly influences the degree of bacterial adhesion to surfaces (Mitik-Dineva et al, 2009;Truong et al, 2010). Cech et al (2013) also observed a reduction of surface roughness for different materials after the coating process.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that the surface roughness of materials strongly influences the degree of bacterial adhesion to surfaces (Mitik-Dineva et al, 2009;Truong et al, 2010). Cech et al (2013) also observed a reduction of surface roughness for different materials after the coating process.…”
Section: Discussionmentioning
confidence: 94%
“…However, for large scale production they lack the wear resistance offered by those materials typically used in industry, such as tool steel. Thermally cured planar HSQ films have previously been used for injection molding [45] and for hot embossing [42], and we have recently observed minimum wear after injection molding >100 000 replicas on planar HSQ films (unpublished results). Above 400 °C, the Si-H bonds in the monomer dissociates and a cross-linked silica network forms, as previously reported and also verified by infrared spectroscopy in the current work (supplementary figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Heat treated HSQ forms a silica-like material that easily reacts with silane-based chemistry employed for applying anti-stiction coatings to the stamp for improved release of polymer replicas [7,19,20,44]. In addition, planar HSQ films have been used as a surface coating on steel molds to lower the surface roughness [45] and we have recently observed an injection molding lifetime of at least 100 000 cycles without measurable wear or defect formation in planar HSQ films of micrometer scale thickness on steel molds (unpublished data). Here, we show an improved filling of nanoscale holes using heat treated nanopatterned HSQ films under isothermal mold conditions compared to an all-metal electroplated nickel shim with an outer chromium/gold coating.…”
Section: Introductionmentioning
confidence: 99%
“…A manufacturing process resembling some of the same methods as presented here, though with a nickel foil used for transferring the nanostructures, has been shown in the literature. [134][135][136] Furthermore, other manufacturing processes associated with additive manufacturing (AM) such as direct laser writing (DLW) allow for creating sub-100 nm structures with similar functionalities as mentioned above. 137 However, the method presented in this work allows for resolutions as achieved in the semiconductor industry and the waferbased platform makes the process competitive to the AM methods in a mass production environment.…”
Section: -63mentioning
confidence: 99%